Rancang Bangun Game Edukasi Media Pembelajaran Bahasa Inggris Menggunakan Pemodelan Finite State Machine - dodik arwin dermawan; Agnesia Putri Yani; Mayloka Yona Charnelia; Satria Dear Rizaldy Abror Cahyono (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2019)
English is an international language, and in Indonesia it can also be a daily language in society. This makes learning English very important to be introduced as a child. The focus of this research is to develop an English language learning media that can attract children's learning interests. The form of learning media based on educational English games, because a child will be more interested if the learning media is full of colors, shapes and characters. The design of this educational game utilizes the Finite State Machine which is a modeling to build the behavior of a non player character (NPC). In this English learning media, NPCs depict enemy characters so that educational games are more interesting to be played by children. The results of this study are a game that can be used as a medium for material enrichment, in the teaching and learning process that is based on the development of information technology. Learning English based on educational games can also attract children's interest, so as to increase the average value of 81.9, compared to conventional English learning when the average value of 67.1